Learning about Chinese Civilization through Historiography and Archaeology - Tungkeunkunt, Kornphanat (Journal of Sinology (วารสารจีนวิทยา), 2017)
This article aims to examine the development of historiography on ancient and pre-historic Chinese civilization and dynamic changes in archaeological findings, with attention to how these have contributed to the establishment of a contemporary intellectual framework for the understanding of the origins of Chinese civilization. Furthermore, it demonstrates that progresses in Chinese archaeology and ancient history have significantly influenced perceptions of Chinese history and civilization.